A Review on the Challenges for Increased Production of Castor - Severino, Liv S.; Auld, Dick L.; Baldanzi, Marco; Candido, Magno J. D.; Chen, Grace; Crosby, William; Tan, D.; He, Xiaohua; Lakshmamma, P.; Lavanya, C.; Machado, Olga L. T.; Mielke, Thomas; et al. (Amer Soc Agronomy, 2012)
Castor (Ricinus communis L.) is one of the oldest cultivated crops, but currently it represents only 0.15% of the vegetable oil produced in the world. Castor oil is of continuing importance to the global specialty chemical industry because it is the only commercial source of a hydroxylated fatty acid. Castor also has tremendous future potential as an industrial oilseed crop because of its high seed oil content (more than 480 g kg(-1)), unique fatty acid composition (900 g kg(-1) of ricinoleic acid), potentially high oil yields (1250-2500 L ha(-1)), and ability to be grown under drought and saline conditions. The scientific literature on castor has been generated by a relatively small global community of researchers over the past century. Much of this work was published in dozens of languages in journals that are not easily accessible to the scientific community. This review was conducted to provide a compilation of the most relevant historic research information and define the tremendous future potential of castor. The article was prepared by a group of 22 scientists from 16 institutions and eight countries. Topics discussed in this review include: (i) germplasm, genetics, breeding, biotic stresses, genome sequencing, and biotechnology; (ii) agronomic production practices, diseases, and abiotic stresses; (iii) management and reduction of toxins for the use of castor meal as both an animal feed and an organic fertilizer; (iv) future industrial uses of castor including renewable fuels; (v) world production, consumption, and prices; and (vi) potential and challenges for increased castor production.